A Review on Graphene-Based Gas/Vapor Sensors with Unique Properties and Potential Applications - Wang, Tao; Huang, Da; Yang, Zhi; Xu, Shusheng; He, Guili; Li, Xiaolin; Hu, Nantao; Yin, Guilin; He, Dannong; Zhang, Liying (Nano-Micro Letters, 2015)
Graphene-based gas/vapor sensors have attracted much attention in recent years due to their variety of structures, unique sensing performances, room-temperature working conditions, and tremendous application prospects, etc. Herein, we summarize recent advantages in graphene preparation, sensor construction, and sensing properties of various graphene-based gas/vapor sensors, such as NH3, NO2, H2, CO, SO2, H2S, as well as vapor of volatile organic compounds. The detection mechanisms pertaining to various gases are also discussed. In conclusion part, some existing problems which may hinder the sensor applications are presented. Several possible methods to solve these problems are proposed, for example, conceived solutions, hybrid nanostructures, multiple sensor arrays, and new recognition algorithm.